Spatiotemporal variability in reef ecology and herbivore impacts in the East Portland Special Fishery Conservation Area, northeast Jamaica (2017-2024) - Williams, Claire M.; Henry, Denise; Martindale, Rowan C.; Gordon-Smith, Debbie-Ann (Frontiers in Marine Science, 2025)
The East Portland Special Fishery Conservation Area (EPSFCA) is a no-take marine reserve in northeast Jamaica, established in 2016. The region is historically understudied and lacks ecological data critical for evaluating conservation outcomes. This study uses monitoring data collected with Global Coral Reef Monitoring Network methods to quantify changes in benthic, fish, and invertebrate communities from 2017 to 2024 and to evaluate the influence of herbivores on reef recovery. Results indicate that fish size and abundance increased between 2017 and 2019 following active enforcement, but these gains declined by 2022 as patrols decreased. In contrast, benthic assemblages showed continued degradation; coral cover declined to ~1% by 2024 alongside rising macroalgae and loss of coralline algae, reflecting disease and heat-stress impacts and a shift toward disturbance-tolerant species. Herbivores such as Diadema antillarum and parrotfish were key in limiting macroalgal dominance, although the intensity of their impact differed among sites. Differences in community composition reflect site-specific variation, indicating that local conditions influence recovery dynamics within the sanctuary. Overall, the EPSFCA demonstrates that consistent enforcement and herbivore protection can promote partial but fragile reef recovery, emphasizing the need for sustained management to rebuild resilience. These results provide a rare long-term assessment for Jamaica’s northeast coast and offer a benchmark for evaluating future conservation outcomes.